Philippine fishes and fisheries. vol. VII. (1936)
contents: Umali, A.F. Edible fishes of Manila./Villadolid, D.V. The Gourami: its cultivation in the Philippines./ Umali, A.F. Deep-sea fishing in the Philippines./Roxas, H.R. The mullet fishery of Naujan, Mindoro./ Manacop, P.R. A new Phallostethid fish with notes on its development./Manacop, P.R. The sexual maturity of some commercial fishes caught in Manila Bay./Roxas, H.A. A fresh-water jellyfish in the Philippines./Roxas, H.A. A checklist of Philippine fishes./Blanco, G.J. Five species of Philippine shrimps of the genus Penaeus./Manacop, P.R. The artificial fertilization of dangit, Amphacanthus oramin (Bloch and Schneider)./Villadolid, D.V. The fisheries of Lake Taal, Pansipit river and Balayan Bay, Batangas province, Luzon./Umali, A.F. The fishery industries of San Miguel Bay./Roxas, H.A. Fresh-water fish farming in the Philippines./Basalan, S.B. Si-si fishery of Samar, Philippine islands./Domantay, J.S. An usual bud due to heteromorphosis in Echinaster Luzonicus (Gray)./Roxas, H.A. A redescription of the genus Mirogobius Herre (Gobiidae)./Manacop, P.R. The fisheries of Lake Mainit and of Northeastern Surigao, including the islands of Dinagat and Siargao.
Keywords: Fishes--collected works; Fishes; Fisheries